2015
DOI: 10.1177/002205741519500202
|View full text |Cite
|
Sign up to set email alerts
|

Engaging African American Males in Reading (Reprint)

Abstract: By providing meaningful reading material and encouraging honest debate, teachers can help African American adolescent males embrace the power of text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 1 publication
1
58
0
Order By: Relevance
“…In particular, leisure reading is correlated with school success including greater vocabulary, reading comprehension, verbal fluency, and content knowledge (Hughes-Hassell & Rodge, 2007;Sells, 2009). Boys, however, lag in reading and pose a particular challenge to engaging in literacy (Banks, 2011;Canadian Council on Learning, 2009;Clark, 2010;Fredrick, 2006;Husband, 2012;Sadowski, 2010;Smith & Wilhelm, 2004;Sokal, 2010;Tatum, 2006;Werderich, 2010). Decades of research and hundreds of studies have identified many factors and proposed many solutions but the dilemma hasn't changed.…”
Section: Boys' Literacymentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, leisure reading is correlated with school success including greater vocabulary, reading comprehension, verbal fluency, and content knowledge (Hughes-Hassell & Rodge, 2007;Sells, 2009). Boys, however, lag in reading and pose a particular challenge to engaging in literacy (Banks, 2011;Canadian Council on Learning, 2009;Clark, 2010;Fredrick, 2006;Husband, 2012;Sadowski, 2010;Smith & Wilhelm, 2004;Sokal, 2010;Tatum, 2006;Werderich, 2010). Decades of research and hundreds of studies have identified many factors and proposed many solutions but the dilemma hasn't changed.…”
Section: Boys' Literacymentioning
confidence: 99%
“…Also, since criminal offenders typically lack empathy (Guerra, 2012), being able to identify with characters in a book is valuable. These urban adolescents really need to see themselves in the protagonists and have the story be culturally relevant to be interested (Husband, 2012;Kirkland, 2011;Moeller, 2011;Tatum, 2006). One student in school said "I like reading books about kids my age that have been abandoned and abused.…”
Section: At-risk Youth and Urban Fictionmentioning
confidence: 99%
See 3 more Smart Citations